O EFEITO DO EDTA SÃ”BRE O FLUXO DE ÃGUA DE CÉLULAS DE Nitella cernua BRAUN - Piccolo, Antonia Lélia G. (REVISTA DE AGRICULTURA, 2016)
O EFEITO DO EDTA SÃ”BRE O FLUXO DE ÃGUA DE CÉLULAS DE Nitella cernua BRAUN